Modelování katastrofických škod - Pacáková, Viera; Kubec, Lukáš (Univerzita Pardubice, 2012)
Catastrophe modelling is a risk management tool that uses computer technology to help insurers, reinsurers and risk managers better assess the potential losses caused by natural and man-made catastrophes. The models use historical disaster information to simulate the characteristics of potential catastrophes and to determine the potential losses cost. The aim of this paper is to describe parametric curve-fitting methods for modelling extreme historical losses. Article summarizes relevant theoretical results above Extreme value theory (EVT) and Excess over Threshold Method (EOT) and provide example of their application to Danish data on large fire insurance losses. Application of these methods is not possible without appropriate software packages. Article refers to these options too.
Modelling of catastrophic losses
Keywords: extreme value theory; generalized pareto distribution; excess over threshold method